A Regional Approach to Health Care Reform. Issue 1 (January 2015) - Rivera, Jose Luis Manzanares; Zuniga, Genny Carrillo
<x xml:space="preserve">Abstract</x> The purpose of this article is to analyze health insurance disparities related to labor environment factors in the Texas-Mexico border region. A logistic regression model was performed using microdata from the 2010 American Community Survey to estimate the probability of having employer-based insurance, controlling labor environment factors such as hours worked, occupation industry, and the choice of private, nonprofit or public sector jobs. Industries primarily employing the Mexican American population are less likely to offer employer-based health insurance. These industries have the North American Industry Classification System (NAICS) code 770 construction, including cleaning, and NAICS code 8680, restaurants and other food services. Although it was found that working in public sector industries such as code 9470, administration of justice, public order, and safety, or NAICS code 7860, elementary and secondary schools, improved by 60% the probability of the Mexican American population having employer-based health insurance, these occupations ranked at the bottom of the main occupation list for Mexican Americans. These findings provide evidence that the labor environment plays an important role in understanding current health insurance access limitations within the Mexican American community under 2010 Patient Protection and Affordable Care Act provisions, which are directed to small business and lower-income individuals.